Prevalence and Determinants of Gastroesophageal Reflux Disease in a Regional Indonesian Hospital Gastroesophageal Reflux Disease: Patterns and Risk Factors in a West Java Hospital Setting - Fatimah, Liliana Surya; Wikarta, Dwi Bayu; Gisrianti, Reina Syafira; Lee, Yeong Yeh (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: Gastroesophageal reflux disease (GERD) is increasing prevalent in Indonesia. However, epidemiology data remain limited, particularly in developing regions such as Karawang. Therefore, this study aims to examine the prevalence, risk factors, and clinical characteristics of GERD within the population of Karawang, West Java.Methods: This study employed a cross-sectional design. Patients aged 18 years who visited the Karawang Regional Public Hospita, were recruited sequentially. Data were collected using a standardized questionnaire. Univariable and multivariable analyses were performed, with a p-value 0.05 considered stastically significant.Results: The prevalence of GERD was 55.6%, with a higher prevalence in women compared to men (58% vs. 42%, p = 0.263). Significant factors associated with GERD included age 40 years (OR = 0.126; 95% CI: 0.043-0.369; p = 0.001), frequent consumption of spicy foods (OR = 5.002; 95% CI: 2.534-9.877; p = 0.001); and NSAIDs consumption (OR = 2.002; 95% CI =2 1.049-3.821; p = 0.035).Conclusion: GERD is prevalent in the Karawang region. Key factors associated with its occurrence include younger age, frequent consumption of spicy foods, and the use NSAIDs.